A Comparison Between Visual, Digital Photography, And Polarizing Filter Photography for Shade Selection Among the Adult Jeddah Population: Life Sciences-Dentistry - Karunakar Shetty, Dr; Alesayi, Farah Khalid; Albakri, Aroub Mohsen.; Balah, Rahaf Qasem.; Alzahib, Ashwag Hussain.; Alunazi, Afrah Mohammed; Alghamdi, Saad Ali A (International Journal of Life Science and Pharma Research, 2023)
Shade selection plays an important role in esthetic dentistry. Modern dentistry has various methods of shade selection, such as visual, digital, and polarized filter methods. Hence, our aim of this study was to determine which of the three named methods was more accurate for shade selection in aesthetic dentistry, and study objectives of the study were to assess the shade of a maxillary central incisor by visual, digital and polarized filter method and to find out which is more suited for shade selection. This clinical observational (analytical, cross-sectional, and descriptive) study was conducted at Ibn Sina National College for Medical Studies, Jeddah. A total of 80 participants were selected randomly. For each all the participants, shade selection was performed by visual, digital, and polarized filter methods. SPSS version 21 was used to perform the statistical analysis. A Chi-square test was applied for qualitative variables to find the association. The level of significance is set at 0.05. Among the participants, 52 (65.0%) participants were female, (35.0%) participants were male, and the minimum age of them was 20, whereas the maximum ages were 50. Among the population pool of the study, 52 (65%) and 28 (35%) participants were female and male, respectively. The minimum age of the participants was 20, and the maximum was 50 years. The study results showed that a polarized filter shade selection method was the most accurate among the three methods of shade selection. It is recommended to select a shade for the esthetic procedures by combining visual, digital, and polarizing filter methods to get accurate shade. It should be added as a part of the curriculum, and emphasis should be given to the various techniques of shade selection.